2008
DOI: 10.1021/la800683m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 10 T External Magnetic Field on the Thermal Decomposition of Fe, Ni, and Co Acetyl Acetonates

Abstract: The current investigation is centered on the thermal decomposition (700 degrees C) of acetyl acetonates of Ni, Co, and Fe in a closed reactor that was conducted by employing an external magnetic field (MF) of 10T. Interestingly, reactions of Co and Ni acetyl acetonates under a 10T MF produce Co and Ni nanoparticles (NPs) coated with carbon, while Fe acetyl acetonate produces Fe3O4 uncoated with carbon. Additionally, it is observed that all the as-formed magnetic particles tend to align in one dimension along a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…19 Thus, laser Raman spectroscopy represents a powerful tool for the in situ investigation of processes of oxidation. Previously, Mossbauer spectroscopy 20 was used to distinguish the difference between Fe 3 O 4 and Fe 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…19 Thus, laser Raman spectroscopy represents a powerful tool for the in situ investigation of processes of oxidation. Previously, Mossbauer spectroscopy 20 was used to distinguish the difference between Fe 3 O 4 and Fe 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the magnetic field strength also has important roles on morphologies of the product. Moreover, the thermal decomposition (700 °C) of acetyl acetonates of Ni, Co in a closed system was conducted by employing a high magnetic field of 10 T. 130 Interestingly, reactions of Co and Ni acetylacetonates under a 10 T magnetic field form Co and Ni nanoparticles coated with carbon. All the as-formed magnetic nanoparticles tend to align in 1D structure along the direction of the magnetic field.…”
Section: Synthesis Of 1d Nanomaterials Under Magnetic Fieldsmentioning
confidence: 99%
“…These experiments confirmed that indeed dry autoclaving process also showed promise for the in situ ordering of magnetic nanoparticles or can remove the carbon coating from the surface of magnetic particle due to their paramagnetic/ferromagnetic apposite interactions under applied magnetic field. With the continued interest, numerous magnetic93–95 or magnetically susceptible96–99 nanomaterials are prepared employing dry autoclaving process.…”
Section: Resultsmentioning
confidence: 99%